TINJAUAN YURIDIS PEMBUKTIAN TERBALIK DALAM PERLINDUNGAN KONSUMEN DI SEKTOR JASA KEUANGAN - Nafis Dwi Kartiko (Jurnal Dialektika Hukum, 2025)
This research explores aspects of reverse proof in consumer protection, particularly in the financial sector. Using a normative juridical approach, this research combines Statutory and Doctrinal Approaches, focusing on the Law of the Republic of Indonesia Number 8 Year 1999 on Consumer Protection and various regulations of the Financial Services Authority. The analysis involves reviewing legal doctrines and related literature to understand the implementation of the reverse proof principle in legal regulations and practices. The results found discrepancies between the theoretical framework of the Consumer Protection Law and actual practice, where the burden of proof is often still placed on the consumer. In the financial services sector, although POJK 6/POJK.07/2022 supports dispute resolution through the Financial Services Sector LAPS by mediation and arbitration, there is a misalignment with the reverse proof principle. In arbitration, both parties, consumer and business, are required to prove their own claims. This finding underscores the need for harmonization between legal theory and practice, particularly in the application of reverse proof for effective and fair consumer protection in the financial services sector.